PENGAWASAN KUALITAS DIMENSI KAYU LAPIS DAN BEBERAPA FAKTOR YANG MEMPENGARUHI DI PT. HUTAN RINDANG BANUA SEBAMBAN BARU TANAH BUMBU - Sari, Fema Novita; Istikowati, Wiwin Tyas; Abidin, Zainal (Jurnal Sylva Scienteae, 2025)
ABSTRACT. The company is currently facing increasingly complex challenges, including in the manufacturing sector. Quality control is essential, even in the field of plywood manufacturing. Quality control of plywood dimensions is crucial to ensure that the produced products meet the expected quality standards. The objective of this research is to determine and analyze the quality of plywood dimensions (length, width, thickness, and curvature) and some influencing factors at PT. Hutan Rindang Banua, Sebamban Baru, Tanah Bumbu. The study conducted quality tests on plywood, including measurements of length, width, thickness, and curvature of 35 samples. The data were analyzed using Shewhart diagrams, and additional information was gathered through interviews and direct field observations. The results of the research showed that the average length of plywood was 2,439.96 mm, and the average width was 1,219.94 mm, both meeting the standard requirements. The average curvature of plywood was 2,729.58 mm, with a non-conformance rate or the probability of not meeting the upper specification limit (ZUpper) of 0.19%. The average thickness of plywood was 12.06 mm, with a non-conformance rate or the probability of not meeting the upper specification limit (ZUpper) of 0.11%, and for the lower specification limit (ZLower), it was 0.14%.Keywords. Fishbone diagram; plywood; Shewhart diagram..ABSTRAK. Perusahaan saat ini menghadapi tantangan yang semakin kompleks, termasuk di sektor manufaktur. Pada bidang kayu lapis pun pengawasan kualitas diperlukan, contohnya pengawasan kualitas dimensi kayu lapis. Pengawasan kualitas dimensi kayu lapis sangat penting untuk memastikan produk yang dihasilkan memenuhi standar kualitas yang diharapkan. Tujuan dari penelitian ini untuk mengetahui dan menganalisis kualitas dimensi kayu lapis (panjang, lebar, tebal dan kesikuan) dan beberapa faktor yang mempengaruhi di PT. Hutan Rindang Banua, Sebamban Baru, Tanah Bumbu. Penelitian melakukan pengujian mutu kayu lapis seperti ukuran Panjang, lebar, tebal, dan kesikuan kayu lapis sebanyak 35 sampel yang dianalisis menggunakan diagram Shewhart serta menggunakan metode wawancara dan observasi lapangan secara langsung. Hasil dari penelitian yaitu ukuran panjang kayu lapis dengan rata-rata 2.439,96 mm dan lebar dengan rata-rata 1.219,94 mm sehingga memenuhi standar, ukuran kesikuan kayu lapis dengan rata-rata 2.729,58 mm tingkat non-konforman atau besarnya peluang tidak terpenuhinya standar batas spesifikasi ZUpper sebesar 0,19%, serta rata-rata tebal kayu lapis 12,06 mm tingkat non-konforman atau peluang tidak terpenuhinya standar spesifikasi ZUpper adalah 0,11%, sedangkan untuk ZLower adalah 0,14%Kata Kunci. Diagram shewhart; diagram tulang ikan;kayu lapis.